2020
DOI: 10.1002/pon.5581
|View full text |Cite
|
Sign up to set email alerts
|

Providing care to parents dying from cancer with dependent children: Health and social care professionals' experience

Abstract: Objective Parents often feel ill‐equipped to prepare their dependent children (<18 years old) for the death of a parent, necessitating support from professionals. The aim of this study is to explore health and social care professionals' (HSCPs) experiences and perceptions of providing supportive care to parents regarding their children, when a parent is dying from cancer. Methods Semi‐structured qualitative interviews were conducted with 32 HSCPs, including nurses, allied health professionals, social workers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 35 publications
3
67
0
Order By: Relevance
“…A similar nding has been reported in the literature [35]. It may be that telling a parent of dependent children that they were eventually going to die from cancer was too big for HSCPs to 'take on', that a more 'comfortable', less personally emotively demanding position for the professional was engaging in physical care needs [20]. However, HSCPs did not acknowledge that hope centred on treatment would eventually place signi cant demands on the well-parent as death approached at the end.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A similar nding has been reported in the literature [35]. It may be that telling a parent of dependent children that they were eventually going to die from cancer was too big for HSCPs to 'take on', that a more 'comfortable', less personally emotively demanding position for the professional was engaging in physical care needs [20]. However, HSCPs did not acknowledge that hope centred on treatment would eventually place signi cant demands on the well-parent as death approached at the end.…”
Section: Discussionsupporting
confidence: 67%
“…Some of the complexities include prognostication being inherently di cult, and the management of patients often complex clinical condition at EOL presiding over the needs of the well-parent and children [21]. Studies highlight insu cient training for HSCPs; therefore, they lack skills, competence and con dence in addressing parents and children's need for support around the time of parental death from cancer [20], with some fearing they could make the situation worse [22]. This is despite national and international end of life guidelines repeatedly acknowledging that families should have honest, sensitive and well-informed conversations about dying, death and bereavement [23].…”
Section: Introductionmentioning
confidence: 99%
“…29,30 It is important that health and social care professionals engage in family-centred conversations with relatives at end of life. 28,31,32 Literature highlights that relatives' desire the opportunity for time with their family member in the final weeks and days of life. 6,10 Alongside this, other studies have reported that providing personal aspects of care or holding a family member's hand has provided comfort and enabled connectedness between relatives and a dying family member at end of life.…”
Section: Discussionmentioning
confidence: 99%
“…3 Challenges that are likely to confront parents throughout this period include a reduced availability for parenting; changes to parental roles; heightened distress as they prepare children for parental death; and, or financial implications. 4,5 One of the intricate and complex challenges faced by parents is how to best prepare and support their children throughout this end of life experience. 5 Children with an understanding of the dying process and are prepared for the death of their parent show quicker adjustment than those not informed.…”
Section: Introductionmentioning
confidence: 99%
“…3 Challenges that are likely to confront parents throughout this period include a reduced availability for parenting; changes to parental roles; heightened distress as they prepare children for parental death; and, or financial implications. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%